Medication Errors, Adverse Drug Events and Cost-Saving in Colorectal Cancer Patients Receiving Chemotherapy by Pharmacist in Sungaikolok Hospital - Tangbowornpichet, Yaowapa (Princess of Naradhiwas University Journal, 2023)
This research aimed to study the type, frequency, and severity of the medication errors, adverse drug events, and the interventions by pharmacist resulting in cost-saving in colorectal cancer patients receiving chemotherapy. A cross-sectional descriptive study was conducted with the data collected from patients diagnosed with colorectal cancer who were receiving chemotherapy at Sungaikolok Hospital within one year. The retrieved data of this study consisted of general data, Medication Error (MEs) using the categorizing from the National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP), Adverse Drug Events (ADEs) according to the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0, and cost-saving intervention in preventable medication errors detected by pharmacist. The results found that there were 20 patients with colorectal cancer who had received chemotherapy. Most of the patients had received the FOLFLOX chemotherapy regimen from 98 prescriptions for chemotherapy medications consisting of 1,225 chemotherapy medication items. The study discovered MEs in 35 prescriptions (35.71%) or 196 chemotherapy items (16.00%). Moreover, the MEs are most found during the prescription process with the severity shown in B and C levels, while the ADEs found were nauseous (46.94%) and fatigued (33.67%). Accordingly, the study also revealed that the pharmacist's intervention led to the cost-saving chemotherapy medication, valued at 109,086.04 Thai Baht, without an ineffective chemotherapy preparation. Therefore, the interventions of pharmacist from chemotherapy preparation unit, in addition to preparing medicines for patients, seeking and solving ADEs and MEs problems allowing the patients to receive the chemotherapy correctly, appropriately, safely, and also contributed to the cost-saving chemotherapy caused by medication errors from prescriptions.